Bivariate Binary Logistic Regression Analysis for Modeling Educational Level and Employment Status in Central Java - Vera Maya Santi; Farah Fadhilah Ridana; Bagus Sumargo (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2025)
Education and employment are two essential components of human development, yet studies that simultaneously examine both outcomes in the context of Central Java remain limited. This research makes a novel contribution by applying bivariate binary logistic regression to jointly model educational attainment and employment status, an approach that has not been previously used for the Central Java population. Using 3,874 observations from the 2024 National Labor Force Survey (Sakernas), the study incorporates two binary response variables and ten predictors to capture the interdependence between education and labor market outcomes. The independence test confirms a significant association between the two responses, supporting the need for a joint modeling framework. Parameter estimation using the Maximum Likelihood method, followed by partial and simultaneous likelihood ratio testing, reveals that marital status and type of institution significantly and simultaneously affect both educational attainment and employment status. The final model achieves classification accuracies of 85.932% and 80.356%, demonstrating strong predictive performance. This study contributes to the literature by presenting an integrated statistical approach that enhances our understanding of how sociodemographic and institutional factors jointly influence human capital and labour participation in Central Java. Keywords: Educational level; Employment status; Bivariate binary logistic regression; Maximum Likelihood method.   Abstrak Pendidikan dan pekerjaan adalah dua komponen penting dari pembangunan manusia, namun studi yang secara bersamaan memeriksa kedua hasil dalam konteks Jawa Tengah masih terbatas. Penelitian ini memberikan kontribusi baru dengan menerapkan regresi logistik biner bivariat untuk memodelkan bersama pencapaian pendidikan dan status pekerjaan, suatu pendekatan yang belum pernah digunakan sebelumnya untuk populasi Jawa Tengah. Dengan menggunakan 3.874 observasi dari Survei Angkatan Kerja Nasional (Sakernas) 2024, studi ini menggabungkan dua variabel respons biner dan sepuluh prediktor untuk menangkap saling ketergantungan antara pendidikan dan hasil pasar tenaga kerja. Uji independensi mengonfirmasi hubungan yang signifikan antara kedua respons, yang mendukung perlunya kerangka kerja pemodelan bersama. Estimasi parameter menggunakan metode Kemungkinan Maksimum, diikuti oleh pengujian rasio kemungkinan parsial dan simultan, mengungkapkan bahwa status perkawinan dan jenis lembaga secara signifikan dan simultan memengaruhi pencapaian pendidikan dan status pekerjaan. Model akhir mencapai akurasi klasifikasi sebesar 85,932% dan 80,356%, yang menunjukkan kinerja prediktif yang kuat. Penelitian ini memberikan kontribusi terhadap literatur dengan menyajikan pendekatan statistik terpadu yang meningkatkan pemahaman kita tentang bagaimana faktor sosiodemografi dan kelembagaan bersama-sama memengaruhi modal manusia dan partisipasi tenaga kerja di Jawa Tengah. Kata Kunci: Tingkat pendidikan; Status pekerjaan; Regresi logistik biner bivariat; Metode Kemungkinan Maksimum. 2020MSC: 62J12, 62P20.